Simulation of repetitive mechanisms using modular kinematics. Issue 1 (8th May 2021) - Simionescu, P.A.
Simulations of several repetitive mechanisms, some of them considered difficult to perform, have been done relatively easily using for loops and the MeKin2D modular-kinematics subroutines. These simulations include generation of multiple couple-curves, wicked-vane and aperture mechanisms, feathering paddlewheels, radial engines and a folding pop riveter. For the former two mechanisms, in addition to motion simulation, shaking-force and mechanical-advantage analyses have also been performed, respectively. For a better understanding of the computer implementations of these simulations, their source code is also provided as an Appendix to the paper.